Media as a determinant of the sexuality of young Poles - Kamila Szymańska; Karolina Widłak; Piotr Pawłowski; Aneta Kościołek; Klaudia Jakubowska (Journal of Education, Health and Sport, 2022)
Objective of the work: The aim of this study is to learn about the influence of the media on the sexuality of young Poles.